2022
DOI: 10.3390/nu14193904
|View full text |Cite
|
Sign up to set email alerts
|

Limonium tetragonum Promotes Running Endurance in Mice through Mitochondrial Biogenesis and Oxidative Fiber Formation

Abstract: The purpose of this study was to examine whether Limonium tetragonum, cultivated in a smart-farming system with LED lamps, could increase exercise capacity in mice. C57BL/6 male mice were orally administered vehicle or Limonium tetragonum water extract (LTE), either 30 or 100 mg/kg, and were subjected to moderate intensity treadmill exercise for 4 weeks. Running distance markedly increased in the LTE group (100 mg/kg) by 80 ± 4% compared to the vehicle group, which was accompanied by a higher proportion of oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Skeletal muscle fiber types are categorized as MyHC (I and IIa) isoforms (oxidative fiber, types I and IIa) and MyHC IIb isoform (glycolytic fiber, type IIb) according to the different myosin heavy chains . Oxidative fibers are rich in mitochondria and myoglobin, while glycolytic fibers have fewer mitochondria and less myoglobin, and mitochondrial biogenesis and function are positively related to oxidative fiber percentage. , A previous study found that a higher proportion of slow oxidative fibers is positively related to good meat quality, but a higher proportion of glycolytic fibers had great tendency to produce pale soft exudative meat . The longissimus dorsi (LD) muscle is classified as a fast glycolytic type, which contains a higher proportion of type IIb fibers, and it is a common sampling site for pork quality research …”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle fiber types are categorized as MyHC (I and IIa) isoforms (oxidative fiber, types I and IIa) and MyHC IIb isoform (glycolytic fiber, type IIb) according to the different myosin heavy chains . Oxidative fibers are rich in mitochondria and myoglobin, while glycolytic fibers have fewer mitochondria and less myoglobin, and mitochondrial biogenesis and function are positively related to oxidative fiber percentage. , A previous study found that a higher proportion of slow oxidative fibers is positively related to good meat quality, but a higher proportion of glycolytic fibers had great tendency to produce pale soft exudative meat . The longissimus dorsi (LD) muscle is classified as a fast glycolytic type, which contains a higher proportion of type IIb fibers, and it is a common sampling site for pork quality research …”
Section: Introductionmentioning
confidence: 99%
“…For example, endurance exercise can induce a transition from fast-twitch to slow-twitch fiber types [6,7]. Consequently, a viable strategy for improving exercise endurance involves targeting the transition from fast-twitch to slow-twitch fiber types [8].…”
Section: Introductionmentioning
confidence: 99%